Association Between Self-Reported Protective Behavior and Heat-Associated Health Complaints Among Patients With Chronic Diseases in Primary Care: Results of the CLIMATE Pilot Cohort Study - Arne Jordan; Julia Nothacker; Valentina Paucke; Klaus Heinz Hager; Susann Hueber; Arian Karimzadeh; Thomas Kötter; Christin Löffler; Beate Sigrid Müller; Daniel Tajdar; Dagmar Lühmann; Martin Scherer; et al. (JMIR Publications, 2024)
BackgroundAs a result of climate change, exposure to high temperatures is becoming more common, even in countries with temperate climates. For patients with chronic diseases, heat poses significant health risks. Empowering patients is a crucial element in protecting the population from the adverse effects of heat. In this context, self-reports of protective behavior are often used to gain a mutual understanding of patients' issues. However, the extent to which self-reported behavior is associated with health complaints remains unclear. ObjectiveThis study aims to describe the association between light to moderate heat and health complaints in everyday life, and to analyze whether self-reported protective behavior and related psychosocial factors are linked to these complaints. MethodsWe conducted a pilot cohort study using internet climate data merged with an online survey of patients with chronic diseases recruited through general practitioner practices. Patients were eligible if they were 18 years or older and had at least one chronic disease. The heat was modeled using temperature and humidity data. Health complaints were assessed through up to 7 follow-up evaluations on the hottest day of each week during the observation period. Data were analyzed using 3 nested models with mixed effects multivariable linear regression, adjusting for random effects at the climate measuring station and participant levels. Model 1 included heat exposure, sociodemographic data, and chronic diseases. Model 2 added protective behavior and health literacy, while model 3 incorporated self-efficacy and somatosensory amplification (ie, the tendency to catastrophize normal bodily sensations such as insect bites). ResultsOf the 291 eligible patients, 61 (21.0%) participated in the study, providing 294 observations. On average, participants were 61 (SD 14) years old, and 31 (51%) were men. The most prevalent conditions were cardiovascular diseases (n=23, 38%) and diabetes mellitus (n=20, 33%). The most commonly reported symptoms were tiredness/fatigue (232/294 observations, 78.9%) and shortness of breath (142/294 observations, 48.3%). Compared with temperatures of 27°C or lower, a heat index between over 27°C and 32°C (β=1.02, 95% CI 0.08-1.96, P=.03) and over 32°C (β=1.35, 95% CI 0.35-2.35, P=.008) were associated with a higher symptom burden. Lower health literacy (β=-0.25, 95% CI -0.49 to -0.01, P=.04) and better self-reported protective behavior (β=0.65, 95% CI 0.29-1.00, P<.001) were also linked to increased symptom burden but lost statistical significance in model 3. Instead, lower self-efficacy (β=-0.39, 95% CI -0.54 to -0.23, P<.001) and higher somatosensory amplification (β=0.18, 95% CI 0.07-0.28, P=.001) were associated with a higher symptom burden. ConclusionsCompared with colder weather, light and moderate heat were associated with more severe health complaints. Symptom burden was lower in participants with higher self-efficacy and less somatosensory amplification. Self-reported protective behavior was not linked to a lower symptom burden. Instead, we found that patients who tended to catastrophize normal bodily sensations reported both better protective behavior and a higher symptom burden simultaneously. Trial RegistrationClinicalTrials.gov NCT05961163; https://clinicaltrials.gov/ct2/show/NCT05961163